Resilient Tradition: The Resilience of Nyekar tradition Amidst the Covid-19 Changes - Pratama, Aldi Rizky (Journal of Contemporary Rituals and Traditions, 2023)
The Nyekar tradition in Sirnaraga Public Cemetery, Bandung, has become an inseparable part of the local community's life. This research aims to understand the sustainability of the Nyekar tradition amidst the Covid-19 pandemic. The study was conducted by documenting and analyzing the Nyekar tradition, describing the condition of Sirnaraga Public Cemetery leading up to Ramadan, and investigating the adaptation of the Nyekar tradition during the Covid-19 pandemic. The research method used was qualitative with a field study approach. The findings show that the Nyekar tradition in Sirnaraga Public Cemetery has remained resilient during the pandemic, with the majority of participants continuing to practice the tradition as usual. This tradition has deep roots in religious, economic, social, and cultural aspects. The sustainability of the Nyekar tradition demonstrates the resilience and adaptation of the community in the face of changes brought about by the pandemic. This research provides a deeper understanding of the sustainability of the Nyekar tradition in Sirnaraga Public Cemetery amidst the Covid-19 pandemic. The implications of these findings can serve as a basis for preserving and promoting the sustainability of this important cultural tradition for the local community.